Pressure dispersion pad use allows patients to kneel comfortably after total knee arthroplasty - Kunihiko Watamori; Kazunori Hino; Tatsuhiko Kutsuna; Tomofumi Kinoshita; Takashi Tsuda; Hiromasa Miura; Masaki Takao (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose This study aimed to clarify the contact pressure at which patients with difficulty in kneeling after total knee arthroplasty (TKA) feel pain and the contact pressure at which kneeling can be performed after using a pressure dispersion pad. Methods Sixty patients (69 knees) who underwent TKA for end‐stage knee osteoarthritis were included. The patients performed single stance kneeling on the sheet‐type pressure mapping system, and the contact pressure and area were measured before and after using the pressure dispersion pad. The Oxford Knee Score was used to evaluate kneeling ability. Results The group of patients who were unable to kneel had significantly lower contact pressure than those who were able to kneel easily (0.61 N/cm2/kg vs. 0.99 N/cm2/kg; p = 0.04). No patient reported kneeling as being ‘impossible’ or ‘extremely difficult’ when using the pressure dispersion pad. Moreover, all patients except those without pain had less pain and improved kneeling scores when using the pressure dispersion pad. Use of the pressure dispersion pad significantly reduced contact pressure for all kneeling score groups after TKA (0.12 N/cm2/kg for the impossible group). Conclusions The patients who could not kneel after TKA felt pain at 61% of the contact pressure compared to those who could kneel easily. Even patients who were unable to kneel after TKA were able to kneel when the contact pressure was reduced to 12% of that of the patients who could easily kneel using a pressure dispersion pad. Level of Evidence Level III.